1996
DOI: 10.1074/jbc.271.26.15458
|View full text |Cite
|
Sign up to set email alerts
|

The KRAB Zinc Finger Gene Encodes an RNA-binding Protein Tightly Associated with the Nuclear Matrix

Abstract: We previously cloned ZNF74, a developmentally expressed zinc finger gene commonly deleted in DiGeorge syndrome. Here, the intron/exon organization of the human gene and the functional properties of the expressed protein are presented. This zinc finger gene from the transcription factor IIIA/Kruppel family contains three exons. A truncated Kruppel-associated box (KRAB) located at the N terminus of the predicted 64-kDa zinc finger protein is encoded by exon 2. The remainder of the protein including the zinc fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 80 publications
1
79
0
Order By: Relevance
“…This result suggests that, in addition to its potential function in transcriptional regulation, ZNF74 may also be involved in RNA metabolism. We also previously reported that ZNF74 is tightly associated with the nuclear matrix, since detergent, DNase, RNase, and high salt treatments could not release it from this nuclear scaffold structure (15). In this study, we report that the ZNF74 zinc finger domain acts as a nuclear matrix targeting sequence.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…This result suggests that, in addition to its potential function in transcriptional regulation, ZNF74 may also be involved in RNA metabolism. We also previously reported that ZNF74 is tightly associated with the nuclear matrix, since detergent, DNase, RNase, and high salt treatments could not release it from this nuclear scaffold structure (15). In this study, we report that the ZNF74 zinc finger domain acts as a nuclear matrix targeting sequence.…”
mentioning
confidence: 61%
“…Although the presence of a KRAB motif and of 12 Cys 2 -His 2 zinc finger motifs suggest that ZNF74 may function as a transcription factor, we recently demonstrated that its zinc finger domain harbors an RNA binding activity in vitro (15). This result suggests that, in addition to its potential function in transcriptional regulation, ZNF74 may also be involved in RNA metabolism.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The SCAN-box is thought to mediate homo-and hetero-dimerization with other SCAN-containing proteins (Williams et al 1999). While most of these proteins have not been functionally characterized so far, individual members of this group have been reported to have roles in binding and splicing of RNA (Grondin et al 1996), or to repress transcription from RNA polymerase I-, II-and IIIpromoters (reviewed by Urrutia 2003).…”
Section: Discussionmentioning
confidence: 99%